Contrasting Views on Physicians in Tobit and Sirach - Chrysovergi, Maria (Journal for the study of the pseudepigrapha, 2011)
This article examines the complex medical situation that lies behind two opposing attitudes about the consultation of physicians and the use of medicines found in the books of Tobit and Sirach. The thesis of this article is that Tob. 2.10 reflects a situation that has emerged due to the experimental stage of pharmacology during the third and second centuries BCE. Sirach 38.1-15, being an indirect response to Tobit’s criticism of secular medicine, attempts to reconcile the medical arts with the biblical belief that God is the only healer (Exod. 15.26). By means of discussion on bodily treatment, both authors venture to construct medical consciousness among the Jewish circles of Second Temple period.